ANALISIS SISTEM AKUNTANSI PENGELOLAAN UANG PERJALANAN DINAS DI INSPEKTORAT IV ITJEN KEMENDIKBUDRISTEK RI - Slamet Soesanto; Haryanto Haryanto (Institut Teknologi dan Bisnis Swadharma, 2021)
Within the scope of government, the Accounting System is a systematic series of procedures, operators, equipment, and other elements to realize the accounting function from transaction analysis to financial reporting within government organizations. As the object and location of research, Inspectorate IV is one of the inspectorates within the Inspectorate General of the Ministry of Education and Culture, where official travel activities are carried out repeatedly by the Government Internal Supervisory Apparatus to support its functions and responsibilities. During the study, the researcher noted that the process of financial administration and management of official travel documents had not been supported by an integrated information system from the issuance of assignment letters to the issuance of official travel receipts. This results in a less effective and efficient process, both in terms of time and budget due to the open level of errors in entering the required data. Administrative Inspectorate IV needs to build an integrated information system for the process of managing official travel in terms of finances and documentation